Faktor-Faktor Yang Menyebabkan Pemberian Kolostrum Pada Ibu Nifas Di Ruang Camar I Rsud Arifin Achmad Provinsi Riau - Na’imatu Shalihah, Liva Maita, (Jurnal Martenity and Neonatal, 2015)
This study aims to determine the factors that led to the provision of postpartum maternal colostrum in the first gulls Arifin Achmad Riau Province Year 2013. This research is quantitative Analytical cross- sectional design . The study population was around the postpartum mothers in Space gulls I Arifin Achmad Riau Province 170 respondents. Bivariate data analysis. The results showed maternal age associated with the administration of colostrum 0024 pvalue≤ 0.05 parity provision of colostrum associated p-value ≤ 0.000 0.05 associated with the provision of education colostrum 0.021 p-value ≤ 0.05 berhubunan family support by giving colostrum p-value ≤ 0.000 0:05 , knowledgerelating to the provision of colostrum 0044 p-value ≤ 0.05 IMD associated with administration of colostrum 0567 p-value ≥ 0:05 .